2017
DOI: 10.1186/s12883-017-0790-9
|View full text |Cite
|
Sign up to set email alerts
|

Content validity and clinical meaningfulness of the HFMSE in spinal muscular atrophy

Abstract: BackgroundReports on the clinical meaningfulness of outcome measures in spinal muscular atrophy (SMA) are rare. In this two-part study, our aim was to explore patients’ and caregivers’ views on the clinical relevance of the Hammersmith Functional Motor Scale Expanded- (HFMSE).MethodsFirst, we used focus groups including SMA patients and caregivers to explore their views on the clinical relevance of the individual activities included in the HFMSE. Then we asked caregivers to comment on the clinical relevance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 16 publications
2
107
0
11
Order By: Relevance
“…While the maximum and long-term response is not yet clear, at the end of the phase III randomised controlled trial on infants with symptomatic SMA type 1, 51% achieved a motor milestone response, including head control (22%), rolling over (10%), sitting independently (8%) and the ability to stand (1%) 9. Stabilisation or some improvement in motor function is considered clinically meaningful by patients and their families,19 and in this context our results suggest a shift in addressing nutritional and pulmonary issues earlier in newly diagnosed patients, and considering introducing proactive measures in the more severe phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…While the maximum and long-term response is not yet clear, at the end of the phase III randomised controlled trial on infants with symptomatic SMA type 1, 51% achieved a motor milestone response, including head control (22%), rolling over (10%), sitting independently (8%) and the ability to stand (1%) 9. Stabilisation or some improvement in motor function is considered clinically meaningful by patients and their families,19 and in this context our results suggest a shift in addressing nutritional and pulmonary issues earlier in newly diagnosed patients, and considering introducing proactive measures in the more severe phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with two recent studies of SMA patients and family conducted in Europe. Pera et al [33] reported that HFMSE instrument items had content validity based on results of focus groups with patients, caregivers and professional. For their participants, the instrument items encompassed important constructs related to meaningful change.…”
Section: Discussionmentioning
confidence: 99%
“…The change values were clustered in three groups: patients with stable results (± 2 points), those with loss of more than 2 points and those with improvements of more than 2 points. The cut‐off of two points was decided on the basis of the experience with the HFMSE and based on patients and carers’ questionnaires reporting that any improvement (equal to two points on the scale) was clinically meaningful to patients and their carers . The percentage of patients within each group were compared across age classes by a chi‐square test (a multinomial model was used to adjust for baseline values).…”
Section: Methodsmentioning
confidence: 99%
“…The cut-off of two points was decided on the basis of the experience with the HFMSE and based on patients and carers' questionnaires reporting that any improvement (equal to two points on the scale) was clinically meaningful to patients and their carers. 7 The percentage of patients within each group were compared across age classes by a chi-square test (a multinomial model was used to adjust for baseline values). Table 1 summarizes the background characteristics of the cohort.…”
Section: Methodsmentioning
confidence: 99%